2020
DOI: 10.1002/jcb.29683
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between miRNAs and signaling cascades of Wnt pathway in chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL), a severe problem all over the world and represents around 25% of all total leukemia cases, is generating the need for novel targets against CLL. Wnt signaling cascade regulates cell proliferation, differentiation, and cell death processes. Thus, any alteration of the Wnt signaling pathway protein cascade might develop into various types of cancers, either by upregulation or downregulation of the Wnt signaling pathway protein components. In addition, it is reported that activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…WNT signaling is a pivotal pathway that regulates various cellular processes during embryogenesis and tumorigenesis. Regarding the post-transcriptional regulatory roles of miRNAs, they can be suggested as modulators of protein components in the WNT pathway [101][102][103]. Gastric cancer (GC) is the most frequent gastrointestinal malignancy and the leading cause of cancer-related mortality in developing countries [104].…”
Section: Wnt and Hedgehog Signaling Pathwaysmentioning
confidence: 99%
“…WNT signaling is a pivotal pathway that regulates various cellular processes during embryogenesis and tumorigenesis. Regarding the post-transcriptional regulatory roles of miRNAs, they can be suggested as modulators of protein components in the WNT pathway [101][102][103]. Gastric cancer (GC) is the most frequent gastrointestinal malignancy and the leading cause of cancer-related mortality in developing countries [104].…”
Section: Wnt and Hedgehog Signaling Pathwaysmentioning
confidence: 99%
“…On the other hand, several findings have noted that some miRNAs are involved in the CLL and ALL pathogenesis intervening the WNT/βcatenin canonical signaling pathway (Bhattacharya et al, 2020;Weerkamp et al, 2006). Recently, it has been confirmed that miR-126 targets the GSK-3β gene and reduces its phosphorylation activity Abbreviations: ALL, acute lymphocytic leukemia; CLL, chronic lymphocytic leukemia; MADD, MAP-kinase activating death domain; mRNA, messenger RNA; miRNA, microRNA; NF-κB, nuclear factor kappa B; NRARP, NOTCH-regulated ankyrin repeat protein; PIK3R2, phosphoinositide-3-kinase, regulatory subunit 2; TGFB, transforming growth factor beta.…”
Section: Wnt/β -Catenin Canonical Signaling Pathwaymentioning
confidence: 99%
“…On the other hand, several findings have noted that some miRNAs are involved in the CLL and ALL pathogenesis intervening the WNT/β‐catenin canonical signaling pathway (Bhattacharya et al, 2020; Weerkamp et al, 2006). Recently, it has been confirmed that miR‐126 targets the GSK‐3β gene and reduces its phosphorylation activity in the CLL cells (Bhattacharya et al, 2020). The miR‐26a is another miRNA directly targeting the GSK‐3β gene.…”
Section: Wnt/β‐catenin Canonical Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The therapy using CAR-T cells represents a recent therapeutic option for some CLL patients [ 40 , 41 ]. Finally, among the promising CLL therapies under investigation targeting several deregulated pathways are the cross-talk between CLL cells, the tumor microenvironment [ 42 , 43 ], the Wnt signaling pathway [ 44 ], various miRNAs [ 45 ], the Notch2 signaling pathway [ 46 ], the mitochondrial metabolism [ 16 ] and the epigenetic modifications [ 47 ].…”
Section: Introductionmentioning
confidence: 99%